Cutting performance and surface integrity during rotary ultrasonic elliptical milling of cast Ni-based superalloy - Zhefei Sun; Yihang Liu; Daxi Geng; Deyuan Zhang; Enze Ying; Runze Liu; Xinggang Jiang (Journal of Materials Research and Technology)
Cast Ni-based superalloys have extensive application in aerospace engine hot end parts, such as tail nozzle adjustment plates, turbine rotors, and guiding devices. Nevertheless, their remarkable mechanical and thermal properties give rise to issues such as poor machinability and surface integrity, and severe tool wear. Rotary ultrasonic elliptical milling (RUEM), a recently developed machining approach that applies ultrasonic transverse vibration to the milling cutter, is evaluated in this study for its effectiveness in controlling surface integrity and tool wear during milling of cast Ni-based superalloys, compared with conventional milling (CM). The findings reveal that RUEM exhibits superior machinability with a maximum force reduction of 25.74% in feed direction and 27.25% in radial cutting depth direction, respectively, compared to that of CM. Additionally, RUEM generates unique microstructure characteristics on the machined surface instead of the obvious feed marks and material flow in CM. The present research also shows that RUEM results in higher and deeper plastic deformation, residual compressive stress and microhardness. Moreover, the total cutting distance in RUEM is improved by 39.88%–44.75% before tool failure, compared to CM. The tool chipping in abrasive wear area in CM is significantly larger than that in RUEM, which result in the tool failure quickly. Besides, RUEM significantly reduces adhesive wear, compared to CM. The adhesive wear area are small pits in RUEM, rather than obvious tool material fall off in CM. These results demonstrate that high-performance machining of cast nickel-based superalloy can be achieved by RUEM.